The most patient man - Khan, Saniyasnain; Anand, Achla Anand, Achla, K. (Goodword Kidz New Delhi, 2003)
"The Most Patient Man" by Saniyasnain Khan is a children's story that recounts the life of Prophet Job (Ayyub), highlighting his remarkable patience and unwavering faith in God through trials and hardships.